Selected practical problems in the judgement concerning drug offences - Błoński, Michał (Acta Universitatis Lodziensis. Folia Iuridica, 2016)
The article raises significant practical problems concerning judgements under the Prevention of Drug Abuse Act. The paper analyses a possibility of discontinuation of the proceedings pursuant to Article 62a of the Act and criticizes in particular the conditions for such a judgement. There are also included some considerations concerning the proper legal classification of the acts referred to in the Prevention of Drug Abuse Act and the term of a “significant amount” of intoxicants or psychotropic substances. A position is expressed that there is lack of a need for statutory clarification of that imprecise concept.